The Effect of Product Innovation on Interest with Satisfaction as Mediation: (a study on Regional Typical Frozen Food Products) - Setiobudi, Auditia (International Business Management - Universitas Ciputra, 2021)
In the future, the food and beverage industry is very promising for industry players due to the trend growth of the food and beverage industry in Indonesia. The food and beverage business is starting to grow rapidly in Indonesia so that it attracts many people to innovate. One form of innovation is the frozen food industry. This study aims to determine the effect of product innovation on repurchase interest by looking at consumer satisfaction as a mediating effect on the frozen food industry. The population in this study were 147 people who were frozen food consumers. Sei. By using a purposive sampling approach and using the Slovin formula, it was determined that the number of samples in this study were 108 respondents. The results of this study indicate that product innovation has a positive and significant effect on customer satisfaction. Product innovation and customer satisfaction have a significant effect on repurchase interest. Consumer satisfaction can mediate the effect of product innovation on consumer repurchase interest. Keywords: Product Innovation; Consumer Satisfaction; Repurchase Interest; Mediation; frozen food.